Experimental and simulation study on the vibration isolation and torsion elimination performances of interconnected air suspensions. (April 2016) - Li, Zhongxing; Ju, Longyu; Jiang, Hong; Xu, Xing; Li, Mei
This paper extends recent research on the dynamic performance of an interconnected air suspension. Although some aspects of the dynamic performance of such suspension systems have been studied, little attention has yet been paid to the torsion elimination performance or to the way in which the form of interconnection influences the interconnecting effectiveness. A model car test bench equipped with interconnected air spring suspensions is constructed and the vibration isolation performances of different interconnections are compared. The test results show that the r.m.s. acceleration value of the vehicle body is reduced by 1.2–6.1% using a lateral interconnection, while it is reduced by 0.1–3.3% using a longitudinal interconnection, because of the longer interconnecting pipes. Further research proves that laterally interconnected air suspensions can gain interconnecting effectiveness by using shorter and thinner interconnecting pipes, and this means that they are more suitable for small- and medium-sized vehicles. When the deformation of the vehicle body is considered, a new eight-degree-of-freedom mathematical model is designed and verified by test examination. This model is used to study the torsion elimination performance, the roll performance and the pitch performance of a laterally interconnected air suspension. It shows that the peak torsional load of the vehicle body under step examination is reduced by 6.68–17.65% on interconnection and, after entering the steady state, the torsional load is almost eliminated. The body roll angle which is caused by the road roughness is reduced by around 6%, while the pitch angle shows little change.